2020
DOI: 10.1111/phpp.12619
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficacy between localized 308‐nm excimer light and targeted 311‐nm narrowband ultraviolet B phototherapy in vitiligo: A randomized, single‐blind comparison study

Abstract: Background There are limited data to compare efficacy between recent 308‐nm excimer and conventional 311‐nm narrowband ultraviolet B (NB‐UVB) light in the treatment of vitiligo. Objective To compare efficacy between 308‐nm excimer light and 311‐nm NB‐UVB in patients with symmetrical vitiligo lesions. Methods Thirty‐six symmetrically paired vitiligo lesions on the same anatomical area were enrolled. One side of the symmetrical lesions was treated with localized 308‐nm excimer light, and the opposite side was tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 39 publications
(51 reference statements)
0
17
0
Order By: Relevance
“…In a recent meta‐analysis, quantitative synthesis of the data from these 2 studies suggested that no significant difference was observed between the combination (PRP +NB‐UVB) and monotherapy (NB‐UVB) groups regarding the clinical improvement 20 . Since the NB‐UVB emission spectrum is close to that of MEL and that both modalities act in vitiligo through the same mechanisms, 21 these findings could also be applied to the combination of PRP and MEL.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent meta‐analysis, quantitative synthesis of the data from these 2 studies suggested that no significant difference was observed between the combination (PRP +NB‐UVB) and monotherapy (NB‐UVB) groups regarding the clinical improvement 20 . Since the NB‐UVB emission spectrum is close to that of MEL and that both modalities act in vitiligo through the same mechanisms, 21 these findings could also be applied to the combination of PRP and MEL.…”
Section: Discussionmentioning
confidence: 99%
“…Hypopigmentation on the face and neck responds more quickly than the extremities (Mehraban & Feily, 2014). Vitiligo lesions on the elbows and knees are less responsive to treatment (Poolsuwan et al, 2021).…”
Section: Fda-approved Treatment Applicationsmentioning
confidence: 99%
“…Phototherapy is a first-line treatment for active nonsegmental vitiligo (Ganzetti et al, 2017). In a study of 36 patients who underwent side-by-side treatment of symmetrical vitiligo lesions, there is a significant reduction in vitiligo severity and higher repigmentation noted on the 308-nm excimer-laser-treated side compared with the 311-nm narrowband UVB (NB-UVB) side (Poolsuwan et al, 2021). Higher treatment efficiency is noted with combination treatment of the 308-nm excimer laser and topical steroids, but limited to no increase in efficacy is noted with topical Vitamin D (Taieb et al, 2013).…”
Section: Fda-approved Treatment Applicationsmentioning
confidence: 99%
“…MEL emits monochromatic wavelengths, providing higher penetration depth and selectively focusing treatment on white spots, which is less likely to cause hyperpigmentation of the surrounding skin. A randomized single-blind controlled study showed that 308 nm excimer phototherapy induced faster pigmentation than 311 nm NB-UVB, 8 but NB-UVB was preferred for extensive (>5% of body surface area) or progressive vitiligo. 9,10 The therapeutic mechanism of NB-UVB in vitiligo involves a variety array of mechanisms.…”
Section: Introductionmentioning
confidence: 99%